Quality of Life and Expressed Emotion in Caregivers of Patients with Psychiatric Disorders - MTP, Sabeena; EJ, Agnes; Rodrigues, Lavina (Journal of Health and Allied Sciences NU, 2023)
Background Caregivers form an integral part of the psychosocial management of patients with psychiatric conditions. Caregivers of patients with major psychiatric disorders feel burdened, as these disorders are unpredictable and long lasting. The study was aimed to assess the quality of life (QOL) and expressed emotion among caregivers of patient's with psychiatric disorders.Materials and Methods A cross-sectional descriptive design was adopted for the study. The sample consisted of 300 caregivers of psychiatric patients who visited psychiatric outpatient department and inpatient department of selected hospital. The caregivers were selected by using convenient sampling technique. Baseline proforma, the World Health Organization Quality of Life Scale (WHO QOL BREF), and Family Attitude Scale were used to collect the data.Results Descriptive and inferential statistics were used to analyze the data. The analysis revealed that there was a weak negative correlation between QOL and expressed emotions. The obtained “r” value (−0.14) was statistically not significant at 0.05 level of significance. Hence, the research hypothesis was rejected and the null hypothesis was accepted.Conclusion The study concluded that there was a low negative correlation between QOL and expressed emotions. The obtained “r” value (−0.14) is statistically not significant at 0.05 level of significance. But there was association between QOL and income and occupation of the caregiver.
Keywords: assess; quality of life; expressed emotion; psychiatric disorder